2013
DOI: 10.1002/2013jc008883
|View full text |Cite
|
Sign up to set email alerts
|

Ground motions on rocky, cliffed, and sandy shorelines generated by ocean waves

Abstract: [1] We compare ground motions observed within about 100 m of the waterline on eight sites located on shorelines with different morphologies (rock slope, cliff, and sand beaches). At all sites, local ocean waves generated ground motions in the frequency band 0.01-40 Hz. Between about 0.01 and 0.1 Hz, foreshore loading and gravitational attraction from ocean swell and infragravity waves drive coherent, in-phase ground flexing motions mostly oriented cross-shore that decay inland. At higher frequencies between 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 25 publications
4
44
0
Order By: Relevance
“…N0.3 Hz (Young et al, 2011), 7-20 Hz (Dickson andPentney, 2012), 1.1-50 Hz (Norman et al, 2013;Vann Jones et al, 2015), 20-45 Hz (Young et al, 2016)). Young et al (2013) observed a range of bands between 2 and 40 Hz across a variety of soft and hard rock cliffs globally. The range of frequency bands observed indicates differences in site response to, and local effects on, wave-cliff impacts.…”
Section: Cliff Ground Motions As Proxies Of Cliff Toe Wave Energymentioning
confidence: 99%
See 4 more Smart Citations
“…N0.3 Hz (Young et al, 2011), 7-20 Hz (Dickson andPentney, 2012), 1.1-50 Hz (Norman et al, 2013;Vann Jones et al, 2015), 20-45 Hz (Young et al, 2016)). Young et al (2013) observed a range of bands between 2 and 40 Hz across a variety of soft and hard rock cliffs globally. The range of frequency bands observed indicates differences in site response to, and local effects on, wave-cliff impacts.…”
Section: Cliff Ground Motions As Proxies Of Cliff Toe Wave Energymentioning
confidence: 99%
“…The range of frequency bands observed indicates differences in site response to, and local effects on, wave-cliff impacts. Young et al (2013) attribute the variability in site response to combinations of tide elevation, wave energy, site morphology and geology and local signal decay. Rock foreshores clearly complicate wave-cliff impact microseismic signals and result in significant variations between even contiguous sites because of the feedbacks between the foreshore and wave breaking and attenuation.…”
Section: Cliff Ground Motions As Proxies Of Cliff Toe Wave Energymentioning
confidence: 99%
See 3 more Smart Citations